2019
DOI: 10.1101/528414
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systems-based map of human brain cell-type enriched genes and malignancy-associated endothelial changes

Abstract: 26

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 91 publications
(137 reference statements)
0
4
0
Order By: Relevance
“…However, we previously showed that unbiased weighted network correlation analysis (WGCNA) (Langfelder and Horvath, 2008), where correlation coefficients between all transcripts are calculated and subsequently clustered into related groups (based on expression similarity), supports Ref.T. based analysis cell type enrichment predictions (Dusart et al, 2019;Norreen-Thorsen et al, 2022). Here, we performed WGNCA of lung and liver samples (Figure S2).…”
Section: Weighted Network Correlation Analysis Supports Cell Type Enr...mentioning
confidence: 83%
See 3 more Smart Citations
“…However, we previously showed that unbiased weighted network correlation analysis (WGCNA) (Langfelder and Horvath, 2008), where correlation coefficients between all transcripts are calculated and subsequently clustered into related groups (based on expression similarity), supports Ref.T. based analysis cell type enrichment predictions (Dusart et al, 2019;Norreen-Thorsen et al, 2022). Here, we performed WGNCA of lung and liver samples (Figure S2).…”
Section: Weighted Network Correlation Analysis Supports Cell Type Enr...mentioning
confidence: 83%
“…Bulk RNAseq datasets for 15 human tissue types were retrieved from Genotype-Tissue Expression (GTEx) V8 (www.gtexportal.org) (Consortium, 2015) (Figure 1A). To identify cell type-enriched transcript profiles, we performed an integrative correlation analysis on each dataset, using our previously published method (Butler et al, 2016;Dusart et al, 2019;Norreen-Thorsen et al, 2022).…”
Section: Cell Type Reference Transcripts Correlate Across Unfractiona...mentioning
confidence: 99%
See 2 more Smart Citations